As expectativas cognitivas na sociedade hipercomplexa: uma leitura das audiências públicas à luz da teoria dos sistemas de Niklas Luhmann. - Silva, Danilma Melo da (2019)
It is expected by the modern society, that the Law is responsible for reducing the Social System’s high complexity. All conceptual construction of the Systems Theory helps to analyze the risk, the complexity and the contingency from a judicial decision, which is a natural act at the court. The decision’s risk, in this work, more specifically, the risk of the legal-constitutional’s decision needs more attention, as it relates to sensitive and paradoxical issues. In this vein, the objective of this study is to re-read jurisdictional public hearings from the Supreme Court, under the systemic legitimization, as they can be considered relevant to help to observe the Legal System. To that end, this study presents the origin and the constitutional basis of the public hearings; it is based on an outline of the systems theory by Niklas Luhmann, as well as on the analysis of four emblematic cases that have been discussed at the Supreme Court, where it is possible to see more clearly the law learning and the connection between the judicial system and others systems such as political, religious, scientific and economic.